Pengambilan Keputusan Menggunakan Analytical Hierarchy Process (AHP) pada Pemilihan Pemasok Produk Lampu - Riska Mulia Arum; Trisna Yuniarti (INVENTORY: Industrial Vocational E-Journal On Agroindustry, 2021)
This study aims to determine the best supplier for in-Lite lighting products. The company chose criteria and sub-criteria in supplier selection to optimize product sales continuity. This study used the Analytical Hierarchy Process (AHP) method, which provided information about the criteria, sub-criteria, and alternatives in the selection of three suppliers: A, B, and C. The existence of priority weights provided a decision in choosing the supplier of the lighting product. The new criteria and sub-criteria were the results of the literature study formulation and then adjusted again with the results of the interview. Seven criteria were determined in this study: production, price, quality, site selection, product suitability, delivery, and service. The results of the calculation of the priority weights of the criteria, sub-criteria, and alternative selection using a questionnaire. The parties involved in the selection of suppliers filled out the questionnaire to obtain a weight for each supplier. Based on the results of AHP calculations, supplier A got the highest weight of 0,442 or 44%, so this supplier is used as a company priority in choosing suppliers for in-Lite type lighting products.